The identification of major component of temu kunci (Kaemferia pandurata Roxb.) essential oils on different altitude (Biodiversitas Journal of Biological Diversity, 2007)
The aims of this study was to know the major component of essential oils of Temu Kunci (Kaemferia pandurata Roxb.) on a different altitude. This research was carried out by method of Stahl destilation at BPTO and GCMS Cromatography at FMIPA UGM for both of from Kerjo (350 m asl) and Jumapolo (450 m asl). The difference of altitude of temu kunciâ€™s lives on, the same of major component of essentialoil but the content among them was different.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: temu kunci, Kaemferia pandurata Roxb., altitude, essential oils.